Evaluation of hydrogen peroxide efficacy against AZD1222 chimpanzee adenovirus strain in the recombinant COVID‐19 vaccine for application in cleaning validation in a pharmaceutical manufacturing industry. (26th December 2021) - Ajorio, A.C.F.B.; Rhodes, V.P.; Rodrigues, A.P.; Diniz, V.A.; Mattoso, J.M.V.; da Silva, I.B.; D`Aiuto, D.M.M.; Brandão, M.L.L.
Abstract: This study aimed to evaluate the performance of hydrogen peroxide vapour (HPV) to inactivate the chimpanzee adenovirus AZD1222 vaccine strain used in the production of recombinant COVID‐19 vaccine for application in cleaning validation in pharmaceutical industries production areas. Two matrixes were tested: formulated recombinant COVID‐19 vaccine (FCV) and active pharmaceutical ingredient (API). The samples were dried on stainless steel and exposed to HPV in an isolator. One biological indicator with population >10 6 Geobacillus stearothermophilus spores was used to validate the HPV decontamination cycle as standard. HPV exposure resulted in complete virus inactivation in FVC (≥5·03 log10 ) and API (≥6·40 log10 ), showing HPV efficacy for reducing chimpanzee adenovirus AZD1222 vaccine strain. However, the optimum concentration and contact time will vary depending on the type of application. Future decontamination studies scaling up the process to the recombinant COVID‐19 vaccine manufacturing areas are necessary to evaluate if the HPV will have the same or better virucidal effectivity in each specific production area. In conclusion, HPV showed efficacy for reducing AZD1222 chimpanzee adenovirus strain and can be a good choice for pharmaceutical industries facilities disinfection during recombinant COVID‐19 vaccine production. Abstract : Significance and Impact of the Study: Hydrogen peroxide vapour showed efficacy for chimpanzee adenovirus AZD1222 strain elimination in two matrixes: formulated recombinant COVID‐19 vaccine (≥5·03 log10 ) and API (≥6·40 log10 ) and can be used in pharmaceutical industries facilities, and can be a good choice for pharmaceutical industries facilities disinfection during recombinant COVID‐19 vaccine production.